Tooth loss in aggressive periodontitis: results 25 years after active periodontal therapy in a private practice - Bäumer, Amelie; Kronsteiner, Dorothea; Staufer, Sebastian; Pretzl, Bernadette; Körner, Gerd; Wang, Yan (Journal of clinical periodontology, 2020)
Aim: To assess tooth loss in patients with aggressive periodontitis (AgP) 10-35 years after active periodontal therapy (APT) in a private practice and to detect possible factors influencing tooth loss. Material and Methods: In 100 patients with AgP, tooth loss was recorded over a median follow-up period of 25.5 years after APT, retrospectively. Patient- and tooth-level factors were assessed with a Cox frailty regression model. Results: Of 2,380 teeth, 227 were lost during a median follow-up time of 25.5 years (2.3 ± 3.6 teeth/patient, range 0-17 teeth), resulting in a mean tooth loss rate of 0.09 teeth/patient/year. At patient-level, statistically significant factors for tooth loss were smoking (p = .039) and the baseline diagnosis generalized AgP (p < .001). Influencing factors at tooth-level were location in the maxilla (p = .003), baseline bone loss (p < .001), molars (p < .001) and premolars (p < .001) as well as abutment teeth (p = .009). Conclusion: Tooth loss occurred rarely in patients with AgP treated in a private practice over a long-time period. Annual tooth loss rates are comparable with those described in university settings. Smoking, generalized form of AgP, location/type of tooth, baseline bone loss and abutment status could be detected as factors impacting upon tooth loss.
First published: 29 November 2019
Gesehen am 12.02.2020